The Effects of Children's Spiritual Coping after Parent, Grandparent or Sibling Death on Children's Grief, Personal Growth, and Mental Health - Hidalgo, Ivette M (ProQuest Dissertations & Theses, 2017)
Parental death can have a negative impact on children’s lives with changes in economic resources, and lead to change in residence, loss of contact with friends and neighbors, change in caretakers, and loss of time with the surviving parent. Research on the effects of a grandparent’s death on children is limited. Death of a sibling signifies the loss of a role model, friend, confidante, and playmate. The purpose of this correlational study was to identify: 1) differences in the spiritual coping strategies used by children across age groups, gender, race/ethnicity, participation in religious rituals and practices, and the relationship of the deceased to the child (parent, grandparent or sibling), and 2) the relationship between children’s use of spiritual coping strategies and grief, personal growth, anxiety, and depression after the death, with and without controls for child’s age, gender, race/ethnicity, participation in religious rituals and practices, and relationship of the deceased to the child. A sample of 97 children, 8 to 18 years old and 64% Hispanic completed the Spiritual Coping Strategies Scale, Hogan Inventory of Bereavement, Spence Children’s Anxiety Scale, and Child Depression Inventory, and their parents completed a demographic form. Children who participated in religious rituals after the death used less religious coping strategies than children who did not participate. When child’s age, gender, race/ethnicity, participation in religious rituals and practices, and relationship of the deceased were controlled, greater use of spiritual coping, but not religious coping, and greater grief were significantly related to greater personal growth and greater anxiety. Younger children and Black children had significantly greater anxiety. Only grief was significantly related to depression. Children who experienced the death of a parent, grandparent, or sibling had similar outcomes. The results of this pioneer study will add knowledge to the state of the science regarding the effects of children’s spiritual coping after parent, grandparent, or sibling death on their grief, personal growth, and mental health which is a subject area were very little is known.